2012
DOI: 10.1002/pc.22301
|View full text |Cite
|
Sign up to set email alerts
|

Transport studies of peanut shell powder reinforced natural rubber composites in aromatic solvents

Abstract: This article investigates the transport behavior of three aromatic organic solvents, viz. benzene, toluene, and xylene in natural rubber (NR) composite membranes containing peanut shell powder (PSP) as filler at different temperatures by conventional weight‐gain experiments. PSP used in compounding the NR was processed in two particle sizes. The solvent swelling characteristics of NR composites containing both untreated and alkali‐treated fillers were investigated. The computed sorption characteristics were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…For the aromatic solvents used in this study, the uptake is in accordance with the solubility parameter difference, i.e., xylene ' toluene ' benzene as shown in Figure 7. Our results agree with the findings of some researchers that used the same type of aromatic solvents [31,32,38,39]. Although several researchers have reported the increase in solvent uptake with decreasing penetrant size [22,38,40,41].…”
Section: Effect Of Penetrant Size On Q Tsupporting
confidence: 83%
See 2 more Smart Citations
“…For the aromatic solvents used in this study, the uptake is in accordance with the solubility parameter difference, i.e., xylene ' toluene ' benzene as shown in Figure 7. Our results agree with the findings of some researchers that used the same type of aromatic solvents [31,32,38,39]. Although several researchers have reported the increase in solvent uptake with decreasing penetrant size [22,38,40,41].…”
Section: Effect Of Penetrant Size On Q Tsupporting
confidence: 83%
“…That the present study has shown a dependence of diffusivity on the molecular mass of solvents. This is in agreement with the findings of some authors [31,32] who reported a direct dependence of diffusion coefficient on the molecular weight and solubility parameter of solvents. The decrease in diffusion coefficient with an increase in temperature as earlier stated may be attributed to the fact that the diffusing molecules are defacilitated by the higher thermal energies at the increased temperature.…”
Section: Diffusion Coefficient (D)supporting
confidence: 82%
See 1 more Smart Citation
“…Prabhakar et al 26 analyzed the effect of peanut shell fillers (without and with a previous alkaline treatment) in epoxy thermosetting resins. In addition, the potential of peanut shell as base material for particle board manufacturing was studied, 27,28 but its use is not generalized. By taking into account the large amounts of peanut shell wastes and considering the increasing concern about environment and sustainable development, new materials are being demanded by our society to give an environmentally friendly solution to wastes.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that modified peanut shell powder composites show better mechanical properties. Also, the transport behavior of benzene, toluene and xylene in peanut shell powder-reinforced natural rubber composite at various temperatures was analyzed by conventional weight-gain experimental method [9] . The estimated Arrhenius activation energies ( E D ) for the sorption, diffusion and permeation process showed the highest E D value in xylene solvent in terms of peanut shell powder contents.…”
Section: Introductionmentioning
confidence: 99%